TANGGUNG JAWAB HUKUM DIREKSI PERSEROAN TERBATAS TERBUKA PADA MEKANISME PELAKSANAAN RUPS SECARA ELEKTRONIK BERDASARKAN POJK 15 TAHUN 2020 - Haerani, Ida (Jurnal De Lege Ferenda Trisakti, 2024)
research discusses the legal responsibilities of directors in conducting electronic General Meetings of Shareholders (GMS) in Public Limited Companies (PT Terbuka), based on Financial Services Authority (OJK) Regulations Number 15 and 16 of 2020. These regulations were issued to facilitate the digital transformation of corporate governance, particularly during the COVID-19 pandemic. The directors are responsible for ensuring that the GMS is conducted in compliance with applicable legal provisions, including the electronic submission of meeting agendas, announcements, and shareholder invitations. This study aims to analyze how these OJK regulations affect the obligations and responsibilities of directors in conducting electronic GMS, as well as the legal implications if the directors fail to fulfill their obligations. The research employs a juridical-empirical method by collecting primary data through interviews and direct observations, along with secondary data from literature reviews. The results show that OJK Regulations 15 and 16 of 2020 have significantly altered the GMS procedures, imposing legal consequences on directors in Indonesia's capital markets